Aromatic rices - Singh, R. K. (Oxford & IBH, 2000)
Aromatic rices are distinct from normal rices in various ways. Besides the differences in fragrance and grain quality characteristics, aromatic rices require different environmental conditions and usually have lower yields. This volume provides in-depth and critical information on all aspects of aromatic rices, including taxonomy and origin, estimation of quality traits, chemistry and biochemistry of aroma, genetics and molecular biology, breeding, factors affecting aroma and other quality traits, crop protection, the status of research and development in different countries and international trade.